The Accountant's Performance and its Influence on Corporate Social Responsibility: english - Guardado Lopez, Sinuhe Carlos (2020)
The mission of all companies involves responding and covering an existing need in society. Companies capture resources from their environment and through their productive activity generate a profit to their shareholders, managers and workers; however, they are not exempt by constitutional mandate to contribute to public spending. Although in recent decades, they have also chosen to harmonize with their environment, generating actions that allow establishing a favorable image before society. One of the professions that are decisive and active in organizational dynamics is accounting, among its many areas of work are: payroll, billing, costs, finances and taxes. In relation to the latter area, the work of the accountant is influential because Mexico is one of the OECD countries that collect less taxes in proportion to its Gross Domestic Product, which is reflected in the resources allocated to public spending. The work of the accountant with adherence to legality, ethics and putting social responsibility firstly is fundamental, since the performance of the accountant has been stigmatized regarding the non-payment of taxes by the taxpayer, even when the latter deliberately opts for not contribute in proportion to public spending. This manuscript exposes the causes of the taxpayer's evasive behavior and the way in which the accountant manages tax matters at the request of the former. This article is product of a bibliographic research and has a descriptive scope.